The factors influence entrepreneur business performance in Incubation Innovation Centre at Technology Park Malaysia / Mohd Nor Fazli Ramli - Ramli, Mohd Nor Fazli (Faculty of Business and Management, 2011)
Incubates or entrepreneurs satisfaction and efficiency of transaction is important for the Incubation Centre at Technology Park Malaysia Corporation as it is show that the Incubation Centre can provide the best services in term of coaching, mentoring, consultancy and training for the new and existing company. In now days, most of the newly formed company had problems in terms of performance because of lack in experience, knowledge, expertise, training, coaching, consultancy and funding. So they cannot operate properly because of the problems that come either expected or unexpected. Therefore, to make sure new or existing companies that used Incubation Centre services are satisfied and comfortable with the environment and services, Incubation Centre must ensure that they will give and provide the best services and help them to recognize the problems and overcome that problems as soon as can. Based on study shows those certain new and existing companies choose Incubation Centre because of the relationship with the state governments are very close and Incubation Centre has the expertise in the field of engineering, biotechnology, business development, it technology and others. It is also why the government encourage the new or existing company work together with Incubation Centre to improve their performance in the businesses.